Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume I Government of Bihar - Planning Commission (Planning Commission, 1985)
Bihar's population of 699 lakhs as per 1981' Census is the second largest among the States of India and constitutes 10.4% of the country’s total population. But in terms of area, Bihar is the Seventh largest State.' The density of population closely follows that of Kerala and West Bengal. 2. Despite 34 years of planning, Bihar continues to be the poorest State in terms of per capita income which was Rs. 995 at current prices in 1981-82 against the All-India per capita income of Rs. 1,758, although the State is endowed with abundant of natural resources of soil, water and mineral wealth. The State is also at the bottom judged from all accepted indicators of development.
Government of Bihar Planning Department